Genome-Wide Analysis on the Landscape of Transcriptomes and Their Relationship With DNA Methylomes in the Hypothalamus Reveals Genes Related to Sexual Precocity in Jining Gray Goats - Su, Feng; Guo, Xiaoli; Wang, Yanchao; Wang, Yuding; Cao, Guiling; Jiang, Yunliang (Frontiers in Endocrinology, 2018)
The Jining Grey goat is famous for its sexual precocity; however, the exact regulatory mechanism is still unknown. The hypothalamus is the key centrum in the process of animal reproduction, especially in signal transduction and the initiation of puberty. The identification of potential genes and pathways in the hypothalamus of Jining Grey goat is critical to understanding the regulatory mechanism of sexual precocity in these goats. In this study, mRNA transcriptome analysis of the hypothalamus of juvenile and pubertal goats revealed eight genes (NTS, ADORA1, CRH, UCN3, E2F2, PDGFRB, GNRH1 and CACNA1C) and three pathways [neuroactive ligand-receptor interaction; gonadotropin-releasing hormone (GnRH) signal; melanoma] that are involved in this regulation. Subsequent methylation analysis on differentially methylated region (DMR) genes revealed the potential regulation network that influences pubertal onset. Correlation analysis verified the methylation level of some DMR genes correlates negatively with expression level. Integrated analysis between transcriptomes and methylomes identified 80 candidate genes involved in GnRH and neuroactive ligand signal pathways, of which CACNA1C and CRH were differentially expressed genes (DEGs) influenced by methylation level. The GnRH gene was the only DEG not affected by its methylation level. In summary, in this study, we identified eight genes and three pathways that are related to pubertal onset in Jining Grey goats, and the expression of CACNA1C and CRH genes of the GnRH and neuroactive ligand signal pathways were influenced by DNA methylation, while that of the GnRH gene was not affected.